Os parques urbanos do século XIX em meio a cidade contemporânea: um estudo comparativo entre o Passeio Público de Curitiba e o Parque Municipal de Belo Horizonte - Izabella Galera (2014)
The public space plays a decisive role in the built environment, establishing itself as an affirmation of the democratic balance between private and public dimension in the city. Its importance in the context of contemporary society goes beyond a symbolic identity, providing a territory for collective manifestations, both as a space for individual expression as an open stage for community life. With the notable urban sprawl we live constantly in large centers, the question is how these urban parks survive amid the contemporary city and how they are being appropriated. The changes that impact on contemporary city produce a new attitude in the understanding of public spaces. The transformation in the economic and social structure, in addition to spatial changes, gives rise to new territoriality, bringing often conflicts between institutional actors and citizens. In this context, public space has a new, political, ideological, social and environmental meaning. This work has as a purpose to analyze the concept of urban park, seeking to understand how Park Américo Renné Giannetti, in Belo Horizonte, and the Public Garden, in Curitiba, have survived among the new demands of the metropolis, as well as trying to establish a relationship between the appropriations of city dwellers with such parks. As a case study, as mentioned before, we have analyzed and compared two parks: Public Garden, located in Curitiba PR, and Park Américo Renné Giannetti, in Belo Horizonte - MG. They have been chosen by being the first parks settled in both capitals, having an importance in historical and cultural context in the latest XIX century. With this proposal, the search enters the main theme " Heritage Management in the Built Environment " , raising the question: how urban parks can contribute to have cities with more environmental awareness, humanized and its recovery as Cultural and Environmental Heritage ?